The Role of Mass Spectrometry to study the Oklo-Bangome Natural Reactors - De Laeter, John; Hidaka, H. (John Wiley & Sons Inc, 2007)
The discovery of the existence of chain reactions at the Oklo natural reactors in Gabon, Central Africa in 1972 was a triumph for the accuracy of mass spectrometric measurements, in that a 0.5% anomaly in the 235U/238U ratio of certain U ore samples indicated a depletion in 235U. Mass spectrometric techniques thereafter played a dominant role in determining the nuclear parameters of the reactor zones themselves, and in deciphering the geochemical characteristics of various elements in the U-rich ore and in the surrounding rock strata. The variations in the isotopic composition of a large number of elements, caused by a combination of nuclear fission, neutron capture and radioactive decay, provide a powerful tool for investigating this unique geological environment. Mass spectrometry can be used to measure the present-day elemental and isotopic abundances of numerous elements, so as to decipher the past history of the reactors and examine the retentivity/mobility of these elements. Many of the fission products have a radioactive decay history that have been used to date the age and duration of the reactor zones, and to provide insight into their nuclear and geochemical behavior as a function of time. The Oklo fission reactors and their near neighbor at Bangombé, some 30 km to the south-east of Oklo, are unique in that not only did they become critical some 2 × 109 years ago, but also the deposits have been preserved over this period of geological time. The long-term geochemical behavior of actinides and fission products have been extensively studied by a variety of mass spectrometric techniques over the past 30 years to provide us with significant information on the mobility/retentivity of this material in a natural geological repository. The Oklo–Bangombé natural reactors are therefore geological analogs that can be evaluated in terms of possible radioactive waste containment sites. As more reactor zones were discovered, it was realized that they could be classified into two groups according to their burial depth in the Oklo mine-site. Reactor Zones 10, 13, and 16 were buried more deeply, and were therefore less weathered than the other zones. The less-weathered zones are of great importance in mobility/retentivity studies and therefore to the question of radioactive waste containment. Isotopic studies of these natural reactors are also of value in physics to examine possible variations in fundamental constants over the past 2 billion years.